Обґрунтування застосування пристроїв плавного пуску в електроприводах занурювальних насосів - Василенков, В.Є. (Енергетика і автоматика, 2017)
THE SUBSTANTIATION OF THE APPLICATION OF DEVICES FOR SMOOTH PUMP IN ELECTRIC DRIVE OF SUBMERSIBLE PUMPS V. Vasilenkov Topicality. It is known that under the tower water supply system for the recovery of water from wells are widely used submersible electric pumps. The submersible electric pump consists of a multi-stage centrifugal pump and a submersible motor. In agriculture ofUkraine, submersible asynchronous electric motors with short-circuited rotors of a series of electric motors with a capacity of 2 to 65 kW are used most often. A characteristic feature of these engines is that they are designed to work under water in wells of small diameter, therefore have enhanced insulation that can work in water, and an elongated body shape. The bearing pair of submersible motors is a pair of slippers: steel-rubber, steel - textolite, plastic steel. The weight of the rotor is perceived by a hexagon consisting of a steel hexagon, planted at the end of the rotor shaft, and a rubber or textolite ring pressed into the groove of the bearing shield. Before turning on the submersible motor into its inner cavity, it is necessary to pour pure water, which cools the windings of the engine and lubricates the bearings.Powerful submersible pumps at start-up due to the large initial dynamic momentum can incite water at the entrance to the sampling filter. In this case, water with a sludge, passing through the engine, falls into the bearings, which leads to a reduction in the life of the engine. Using a regulated electric drive, you can smoothly start the pump installation and prevent possible percolation of water in the intake.Thus, the use of modern technologies to reduce the dynamic moments is an urgent task.Analysis of recent researches and publications. The peculiarity of asynchronous motors with short-circuited rotors during direct start-up is a large starting current, which is 3.5 ... 8 times larger than the nominal and large starting torque, the multiplicity of which reaches (1.4 ... 2.2) . [3]. To prevent overheating of the engine by starting currents, the starting frequency should not exceed 3 times per hour. . [1-4]. Improving the reliability of submersible pumps by reducing dynamic moments is an issue that needs a modern solution. Different methods are used to achieve this goal, one of which is the use of smooth start devices [3]. This technology has a number of advantages, and the main one is the smooth increase in voltage on the windings of the electric motor. This allows it to keep the parameters of the electric motor within safe limits during the start, which reduces the probability of overheating of windings and prevents jerks in the mechanical part of the drive, as well as the probability of hydraulic shocks in pipes and latches at the time of start and stop, which increases the durability and reliability of the electric motor and its driveThe purpose of research. Investigation of the dynamics of the inclusion of a submersible pump to improve the functioning of water supply systems in rural areas as a way of saving energy resources and rational working regimes          Materials and methods of research. Passport characteristics of the submersible pump of the mark ECV-8-40-90, with the electric motor-EDV-22-180 and the device of smooth start-up VLT®MCD 100. Method of construction of the mechanical characteristics of the electric motor with a smooth start device and without it.Research results. To study the dynamics of the inclusion of a submersible pump in the work, for example, we will take an electric pump unit with the following passport characteristics: the pump - ECV-8-40-90, Pm = 19.5 kW, the engine - ПЭДДВ-22-180; Rn = 22kW, In = 48.5A, n = 2850rpm, η = 0.86, cos f = 0.8, S = 3.3%, Mmax / Mn = 2, Mmin / Mn = 0.7, Run / Mn = 0.85, In / In = 7, the VLT®MCD 100 soft start device is selected according to the characteristics of the submersible pump and the possibilities of adjusting the torque reduction on the motor shaft in the range of 30 and 80% of the nominal torque. To determine the quantitative parameters of the moment on the shaft of the electric motor, we use the method of calculation and construction of the mechanical characteristics of the electric motor according to the passport data [3] with subsequent author's peculiarities of calculation and construction of a modified form of mechanical characteristics of the electric motor, which is the direction of implementation of energy saving technologies.Conclusions 1. Using a phase-controlled RFT consisting of three pairs of oppositely-parallel switched thyristors and allowing to regulate the pressure of the blood pressure at its constant frequency by changing the angle of opening of the thyristors, allows the regulation of the starting torque of the electric motor by the PLC device from 18.7 to 67.9 Nm in relation to the nominal 73.3, which is in the percentage ranging from 25.5 to 67.9 %.2. With a smooth start-up, the term of the fail-safe operation is increased by 10 ... 15 % and will be within the range of 39600 ... 41400 h. against a standard 36,000 hours.